MONITORING OF VARIOUS TYPES OF NEUROMUSCULAR BLOCKADE - N. V. Chubchenko; K. M. Lebedinskiy (Вестник анестезиологии и реаниматологии, 2018)
Goal of the review: to build up the current understanding of electrophysiological specific features of various neuromuscular blockades. Having analyzed the results of multiple studies devoted to investigation of the impact of various medications including inhalation anesthetics on the neuromuscular neurility, the authors summarized the current opportunities to monitor neuromuscular blockade. It has been noted that the data for blockade monitoring when using traditional neuromuscular blocking agents are studied much better compared to the drugs providing the other types of blockade.